Microenvironmental Factors Drive Tenascin C and Src Cooperation to Promote Invadopodia Formation in Ewing Sarcoma - Allegra G. Hawkins; Claire M. Julian; Sonja Konzen; Sydney Treichel; Elizabeth R. Lawlor; Kelly M. Bailey (Neoplasia: An International Journal for Oncology Research, 2019)
Ewing sarcoma is a bone tumor most commonly diagnosed in adolescents and young adults. Survival for patients with recurrent or metastatic Ewing sarcoma is dismal and there is a dire need to better understand the mechanisms of cell metastasis specific to this disease. Our recent work demonstrated that microenvironmental stress leads to increased Ewing sarcoma cell invasion through Src activation. Additionally, we have shown that the matricellular protein tenascin C (TNC) promotes metastasis in Ewing sarcoma. A major role of both TNC and Src is mediation of cell–cell and cell-matrix interactions resulting in changes in cell motility, invasion, and adhesion. However, it remains largely unknown, if and how, TNC and Src are linked in these processes. We hypothesized that TNC is a positive regulator of invadopodia formation in Ewing sarcoma through its ability to activate Src. We demonstrate here that both tumor cell endogenous and exogenous TNC can enhance Src activation and invadopodia formation in Ewing sarcoma. We found that microenvironmental stress upregulates TNC expression and this is dampened with application of the Src inhibitor dasatinib, suggesting that TNC expression and Src activation cooperate to promote the invasive phenotype. This work reports the impact of stress-induced TNC expression on enhancing cell invadopodia formation, provides evidence for a feed forward loop between TNC and Src to promote cell metastatic behavior, and highlights a pathway by which microenvironment-driven TNC expression could be therapeutically targeted in Ewing sarcoma.